2022
DOI: 10.1021/acs.chemmater.2c00304
|View full text |Cite
|
Sign up to set email alerts
|

Eu5Al3Sb6: Al4 Tetrahedra Embedded in a Rock-Salt-Like Structure

Abstract: The new Eu 5 Al 3 Sb 6 phase has been successfully synthesized as a pure phase through Sn flux methods yielding large, high-quality crystals. This structure type features disordered Al clusters that appear in the form of dual tetrahedra. It crystallizes in the monoclinic C2/m space group exhibiting a rock-salt-like Eu−Sb framework with [Al 4 ] tetrahedra replacing some of the cationic Eu atoms (space group: C2/m, a = 8.151(1) Å, b = 14.181(2) Å, c = 8.145(1) Å, β = 109.577(2)°). The structure models the [Al 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…To negate some of these effects, 4f orbitals were either excluded from the calculations or treated as core states in Eu 8 Zn 2 As 6 O and Eu 14 Zn 5 As 12 O, thus minimizing the influence of half-filled 4f orbitals, as expected for Eu 2+ species. This approach is widely used for Eu- and Yb-containing compounds, providing a reliable basis for preliminary analysis of the electronic structure. , …”
Section: Resultsmentioning
confidence: 99%
“…To negate some of these effects, 4f orbitals were either excluded from the calculations or treated as core states in Eu 8 Zn 2 As 6 O and Eu 14 Zn 5 As 12 O, thus minimizing the influence of half-filled 4f orbitals, as expected for Eu 2+ species. This approach is widely used for Eu- and Yb-containing compounds, providing a reliable basis for preliminary analysis of the electronic structure. , …”
Section: Resultsmentioning
confidence: 99%
“…This is especially true when scattering cross-sections are similar among constituent species. For example, inorganic pseudobinary clathrates are most often reported with mixed occupancy among the framework sites 25,26,64 , and ambiguous chemical ordering is common among materials containing vacancies 23,24,28,29 . Recent studies have demonstrated substantial variation in SOF in pseudobinary inorganic clathrates, according to chemical composition, temperature, and synthesis method 25,26 .…”
Section: A Chemical Orderingmentioning
confidence: 99%
“…For example, inorganic pseudobinary clathrates are most often reported with mixed occupancy among the framework sites, 25,26,64 and ambiguous chemical ordering is common among materials containing vacancies. 23,24,28,29 Recent studies have demonstrated substantial variation in SOF in pseudobinary inorganic clathrates, according to chemical composition, temperature, and synthesis method. 25,26 Additionally, site occupation factors can impact the mechanical, electronic, and thermal properties of a material.…”
Section: A Chemical Orderingmentioning
confidence: 99%
“…The recent discovery of chemically driven superstructural ordering, [20][21][22] vacancy-ordering, 23,24 and order-disorder phase transitions 25,26 provides strong motivation for determining favorable decoration in large crystals. Nonetheless, characterizing the energetic influence of atomic interchange within a fixed geometry is useful for other endeavors, such as introducing dopants at various concentrations, selecting the optimal location of vacancies, resolving coordination in systems with mixed site occupancy, [27][28][29] or making atomic substitutions of any kind.…”
Section: Introductionmentioning
confidence: 99%